Regulatory T cells trigger effector T cell DNA damage and senescence caused by metabolic competition - Xia Liu (Nature Portfolio, 2018)
Regulatory T (Treg) cells can induce senescence of tumour-associated effector T cells, but it is not clear how. Here the authors show that Treg cells outcompete effector T cells for glucose uptake, resulting in activation of the DNA damage response in effector T cells.